Editorial - Comité Editorial, FII (1998)
In the XXI century it is necessary to start doing exercises abstraction abandoning the overly analytical approach we tend to human nature. We live in a real battle daily goals and objectives that we require at least occasionally turn away from this partial reality to observe the most distant future where we lead our steps. If we consider the relationship between science, technology and society, as a basis for sustainable development in our country, we will have our hands on the tool that allows us to have such a vision.